RURAL WOMEN: THE CASE OF LAS VIRTUDES IN SANTA CRUZ, TURRIALBA - Cubillo Mora, Mayela (2014)
This article analyzes the participation of rural women in the productive and reproductiveprocess, the invisibility of their work in agricultural households and their reproductive rolein a double shift. Particularly, at Las Virtudes in Santa Cruz of Turrialba, the importanceof family is recognized in the development of this community and the study of their membersshows the naturalization of the subordinate role of rural women, despite working inthe same conditions than men.